Regions of poliovirus protein VP1 produced in Escherichia coli induce neutralizing antibodies. - Hoatlin, M E (1987)
Poliovirus type 1 cDNA was prepared from viral RNA encoding the VP1 capsid region of the virus by using a specific DNA primer and was cloned in Escherichia coli. DNA fragments corresponding to VP1 amino acid positions 129 to 302 (pPM5k3), 52 to 302 (pPMhae3), and 24 to 129 (pPMDxba) were incorporated into plasmid vectors designed to express Trp LE-poliovirus VP1 fusion proteins under the control of the inducible tryptophan promoter-operator system. Induction of bacterial cultures containing the plasmids resulted in the production of fusion proteins which accounted for 21% (pPMhae3), 68% (pPM5k3), and 27% (pPMDxba) of the total cell protein. The proteins were purified, and each reacted with polyclonal antibodies raised against intact virions as measured by an enzyme-linked immunosorbent assay. The sera from rabbits immunized with the bacterially produced fusion proteins pPMDxba and pPMhae3 contained poliovirus-neutralizing antibodies.